Exploring Language Ideologies and Preparing Preservice Teachers for Multilingual and Multicultural Classrooms. (November 2019) - Lew, Shim; Siffrinn, Nicole E.
This study explores the language ideologies of preservice teachers (PTs) in undergraduate English for Speakers of Other Languages courses. In particular, it examines 200 PTs' written reflections to better understand how they conceptualize the role of language in their lives and how they use their experiences to make sense of linguistic diversity in the K–12 classroom. Using the tenets of grounded theory and the interpersonal metafunction of systemic functional linguistics, four themes emerged from the analysis: (1) messages received from parents or guardians about "proper" language use, (2) the impact of language on their identity development, (3) the significance of direct experiences on language acceptance, and (4) the acknowledgment yet perpetuation of linguistic discrimination. Implications include the need to integrate more linguistically responsive approaches to working with English learners in PT education curricula.